PENGEMBANGAN APLIKASI DASHBOARD RUMAH SAKIT (Information Technology and Telematics, 2015)
Abstract With the strength of the era of globalization has been very rapid delivery of information, chiefly in informing a hospital. Hospital as a professional health care institutions that provide services in olehn doctors, nurses and other experts. The information is intended to make it easier for hospital staff to obtain the data without having to look at the database one by one. Use of this hospital dashboard application is a combination of pain eumah applications using the web service, which later as a bridge to display the data. And the end result will form a dashboard display to display the information in the form json dat so that the information obtained can be known by the hospital staff effectively. The results of this study aims to facilitate in terms of presenting an information effectively, fast and exciting, visualization dashboards that appear in the form Recap Patient data per month, per Patient Data Recap Sunday Recap per Disease Patient Data and Patient Data Recap per room. Keywords: Visualization Dashboard, Json, Web service